AMPK Regulation of Myeloid Inflammatory Responses During Acute and Chronic Disease - Smith, Tyler (Université d'Ottawa / University of Ottawa, 2025)
AMPK is a heterotrimeric kinase that shifts cellular metabolism to favour catabolism once activated by changes in glucose, adenine nucleotide, fatty acid, or calcium levels. Innate immune cells such as macrophages must rewire metabolic signaling to efficiently respond to inflammatory insults. In this dissertation, we aim to link AMPK-mediated changes in metabolism to immune cell function under several inflammatory states including atherosclerosis and bacterial infection. To begin, we examine a downstream target of AMPK in the cholesterol synthesis pathway, HMG-CoA reductase, which has links to the cholesterol-driven pathology of atherosclerosis. By using a combination of mouse and cell models that lack the inhibitory AMPK phosphorylation site on HMG-CoA reductase, we establish that this signaling axis does not significantly impact atherosclerosis progression. This work highlights the importance of preclinical atherosclerosis model selection and the context-dependent roles of AMPK in atherosclerosis. Next, we investigate how AMPK activity influences macrophage function in the response to infection with Salmonella enterica serovar Typhimurium (S.Tm). We observe that pharmacological AMPK activation in macrophages suppresses a subset of NF-𝜅B-dependent target genes during infection. Metabolomics data suggest that activating AMPK rewires nitric oxide, TCA, and pyrimidine synthesis metabolism in infected macrophages. Mice expressing overactive AMPK (β1/β2-G2A) succumb to S.Tm infection earlier than wild-type mice, though mice treated with the allosteric activator, MK-8722, are unaffected. These data support how AMPK plays distinct roles during gram-negative bacterial infection at the cellular and systemic levels. Finally, we interrogate the effects of AMPK β subunit myristoylation and how it affects AMPK protein stability. We measured AMPK protein levels in cells and mice lacking the AMPK myristoylation site (β1/β2-G2A) and observed a strong decrease in steady state 𝛾 subunit levels alongside more mild decreases in ɑ and β subunit levels. These were unaffected by proteasomal inhibition, and knockdown of proposed myristoylation-dependent E3 ubiquitin ligases ZYG11B and ZER1 had no effect on AMPK protein levels. We conclude that non-canonical regulators of protein stability must influence non-myristoylated AMPK protein levels. Collectively, this work advances our understanding of AMPK function within immune cells and during inflammatory disease progression.
Keywords: Metabolism; Inflammation; AMPK; Salmonella; Atherosclerosis; Proteostasis; Myristoylation